Early alpha power in the frontal lobe area can predict delirium after cardiac surgery - Fengbo Pei; Xupeng Yang; Pengfei Chen; Jinhua Wei; Yao Yao; Zhou Zhao; Hui Wu; Yi Shi; Zujun Chen (Journal of Cardiothoracic Surgery)
Abstract Background Delirium is a common postoperative complication in patients undergoing cardiac surgery and is associated with prolonged hospitalization and persistent cognitive impairment. This study aimed to assess the predictive value of alpha power in various brain regions at different time points for postoperative delirium. Methods Patients scheduled for routine cardiac surgery were prospectively enrolled. All participants underwent 12-hour ambulatory electroencephalography (EEG) monitoring immediately upon admission to the intensive care unit (ICU). Delirium was assessed daily using the CAM-ICU criteria for five postoperative days. Alpha power in the frontal, parietal, and occipital lobes was analyzed at three time points: immediately (T0), at 6 h, and at 12 h postoperatively. Results Among the 106 patients in the training cohort, 45 developed postoperative delirium. These patients had a higher incidence of hypertension and prolonged extracorporeal circulation and aortic clamping times. Alpha power in the frontal lobe at T0 was identified as the most accurate predictor of delirium, with an area under the curve (AUC) of 0.91 (95% CI: 0.84–0.97). The validation cohort (n = 74) showed consistent results with an AUC of 0.9188 (95% CI: 0.87–0.99; P < 0.001). Conclusion Frontal lobe alpha power measured immediately postoperatively could be a reliable neurophysiological biomarker for predicting delirium after cardiac surgery, outperforming conventional clinical predictors (AUC 0.91 vs. 0.70). Graphical Abstract